The clinical value of neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, and D-dimer-to-fibrinogen ratio for predicting pneumonia and poor outcomes in patients with acute intracerebral hemorrhage - Luo, Sai; Yang, Wen-Song; Shen, Yi-Qing; Chen, Ping; Zhang, Shu-Qiang; Jia, Zhen; Li, Qi; Zhao, Jian-Ting; Xie, Peng (Frontiers in Immunology, 2022)
Objective This study aimed to investigate neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and D-dimer-to-fibrinogen ratio (DFR) as predictors of pneumonia and poor outcome in patients with acute intracerebral hemorrhage (ICH). Methods We retrospectively examined patients with acute ICH treated in our institution from May 2018 to July 2020. Patient characteristics, laboratory testing data, radiologic imaging data, and 90-day outcomes were recorded and analyzed. Results Among the 329 patients included for analysis, 183 (55.6%) developed pneumonia. Admission systolic blood pressure, initial hematoma volume, D-dimer concentration, NLR, PLR, DFR, and white blood cell, platelet, neutrophil and lymphocyte counts were significantly higher in patients who developed pneumonia than in those who did not;, admission GCS score was significantly lower in the pneumonia patients (all P <0.05). Multivariate logistic regression showed that NLR and PLR were independent predictors of pneumonia;, NLR and DFR were independent predictors of poor 90-day outcome (modified Rankin scale score 4–6). Conclusions NLR and PLR were independent predictors of pneumonia. NLR and DFR were independent predictors of poor 90-day outcome. NLR, PLR, and DFR can provide prognostic information in acute ICH patients.